You are the brand - Adubato, Steve (Rutgers University Press, 2011)
"Steve Adubato's entire professional life has been about branding-learning it, living it, making mistakes at it, teaching it at several universities, while discovering how to find the fine line between shameless self-promotion and smart, strategic branding-first for himself, then for others, and now for readers interested in an honest analysis of the good and bad in practiced branding. In You Are the Brand Adubato profiles the brands of more than thirty people and companies and skillfully analyzes and dissects their strategies"--Provided by publisher.